RETRACTED: Cellular functions of spermatogonial stem cells in relation to JAK/STAT signaling pathway - Guo, Xinyu; Dong, Liang; Hao, Dingjun (Frontiers in Cell and Developmental Biology, 2024)
This manuscript comprehensively reviews the interrelationship between spermatogonial stem cells (SSCs) and the JAK/STAT signaling pathway. Spermatogonial stem cells in the testes of male mammals, characterized by their self-renewal and pluripotential differentiation capabilities, are essential for tissue regeneration, immunomodulation, and advancements in regenerative medicine. This review delves into the historical background and biological characteristics of SSCs, with a particular emphasis on the pivotal role of the JAK/STAT signaling pathway in their proliferation, maturation, and differentiation processes. Research indicates that the JAK/STAT pathway extensively influences various functionalities of spermatogonial stem cells, encompassing immunomodulation, tissue differentiation, homing, and adaptation to the microenvironment. Herein, we collate and dissect related studies, shedding light on the intricate dynamics between SSCs and the JAK/STAT signaling pathway, and examine the implications of these interactions on the biological attributes and functionalities of SSCs. Furthermore, the review discusses the profound implications of these findings for preclinical research and the domain of cellular engineering. It is acknowledged that, despite advancements in the research of SSCs and the JAK/STAT signaling pathway, investigations in humans and larger mammals remain inadequate, necessitating more in-depth exploration to establish a comprehensive theoretical framework. Overall, this review offers an invaluable reference for deciphering the mechanisms of the spermatogonial stem cell signaling pathways and establishes a theoretical groundwork for related preclinical research.